2017
DOI: 10.1177/0049475517743360
|View full text |Cite
|
Sign up to set email alerts
|

Stenotrophomonas maltophilia causing blood stream infection in neonates and infants: a cause for concern

Abstract: Stenotrophomonas maltophilia ( S. maltophilia) is an important Gram-negative, non-fermentative, multidrug resistant (MDR) nosocomial organism. We evaluated the isolation of S. maltophilia from the seven blood culture specimens received from the Paediatric Emergency Department (PED) of BP Koirala Institute of Health Sciences (BPKIHS) over the duration of two weeks. The suspicion of a possible outbreak was raised and the hospital infection control team investigated the source and found the hand of one healthcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Finally, identification of the non-fermenters, P. aeruginosa, S. maltophilia, and A. baumannii will support the escalation of therapy, while broadening coverage to include the multi-drug resistance (MDR) of these bacteria (32)(33)(34)(35). The BCID-GN can provide information to hospital epidemiologists, infection preventionists, and bed management teams by providing faster Downloaded from https://journals.asm.org/journal/jcm on 13 July 2021 by 44.224.250.200. identification of MDR microbes, upon which to base isolation practices for microbes with the potential for healthcare-associated outbreaks (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, identification of the non-fermenters, P. aeruginosa, S. maltophilia, and A. baumannii will support the escalation of therapy, while broadening coverage to include the multi-drug resistance (MDR) of these bacteria (32)(33)(34)(35). The BCID-GN can provide information to hospital epidemiologists, infection preventionists, and bed management teams by providing faster Downloaded from https://journals.asm.org/journal/jcm on 13 July 2021 by 44.224.250.200. identification of MDR microbes, upon which to base isolation practices for microbes with the potential for healthcare-associated outbreaks (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…When examining outbreaks due to S. maltophilia reported in the literature, it was found that water and medical equipment were identified as possible sources in the foreground. However, outbreaks can be seen in different forms, such as in the contamination of dialysates used in dialysis centres or acute endophthalmitis outbreaks detected in eye centers where intravitreal injections are applied [13][14][15]. A study conducted in Mexico examined the blood and urine cultures of pediatric patients in the emergency room together with 21 S. maltophilia isolates taken from the taps of the same unit and found a total of 7 PFGE clones with 52% genetic variation [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is a known cause of VAP and carries a high morbidity and mortality risk in neonates. 9,10 Treatment of infections caused by S. maltophilia may be a therapeutic challenge due to intrinsic resistance to multiple antibiotics, including carbapenems. Trimethoprim-sulfamethoxazole (TMP-SMX) is the mainstay of S. maltophilia treatment in adults, but can be challenging to administer in the neonate due to concerns of hyperbilirubinemia, bone marrow suppression and limited published data pertaining to appropriate dosing.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these antibiotics has been well studied in the preterm neonatal population for S. maltophilia infection. While there are no published CLSI susceptibility criteria for ciprofloxacin in treating S. maltophilia infections, it has been used successfully as monotherapy in a case of neonatal meningitis with bacteremia (20 mg/kg/d) 17 ; and in a cluster of 7 preterm neonates with bacteremia 9 ; as well as via topical nephrostomy tube instillation for a complicated S. maltophilia urinoma infection. 18 Amikacin and intravenous chloramphenicol (50 mg/kg/d) have been used in case studies for the treatment of S. maltophilia subdural empyema and intracranial abscess in a term neonate.…”
Section: Discussionmentioning
confidence: 99%